Anemia: a non-communicable disease, its prevalence in adult patients of Telangana region of South India; a semi-urban tertiary care teaching hospital study - Jatav, Rajendra Kumar; Kumbhare, Mamta B.; Rao, Pekra Ragini; Reddy, Alugubelly Keerthi; Chennamaneni, Rachana (International Journal of Advances in Medicine, 2017)
Anemia is a one of the major health challenges to global development in this century and this non-communicable disease is rapidly rising in both developed and developing countries. Anemia is wide spread in India but it varies in severity from state to state and zone to zone. Poor diet, lack of sense of hygiene which lead to worm infestations, lack of health consciousness, social taboos and poor economic status all contributes to overwhelming prevalence of anemia. Our analysis suggests prevalence of anemia is very high in adult age group and especially in female patients. Chronic anemia’s have significant morbidity and mortality in untreated patients, because anemia is a sign, not a diagnosis, an evaluation is almost warranted to identify the underlying cause.